INTERNATIONAL ASPECT OF RESEARCH OF THE ENVIRONMENT OF FUNCTIONING OF INDUSTRIAL ENTERPRISES OF UKRAINE, FROM THE POSITION OF ENSURING ECONOMIC SECURITY - LIUBOKHYNETS, LARYSA; RUDNICHENKO, YEVHENII; HAVLOVSKA, NATALIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In the article presents the results of the analysis of the current state of the environment of enterprises from the standpoint of ensuring economic security at the level of national economy and countries. The main trends of dynamic changes in business conditions based on the analysis of international indicators are identified. Indicators of rating assessment of Doing Business  conditions and their dynamics in modern conditions of ensuring economic security of enterprises are characterized.The economic security of domestic enterprises significantly depends on the influence of external and internal factors. Such factors change quite strongly in accordance with global trends in socio-economic processes, as well as reflect the national characteristics of the economy. Factors influencing the development of industrial enterprises and their economic security can be analyzed through a rating assessment of Doing Business, which is the basis for deregulation of the national economy.According to the Doing Business report, from May 2018 to April 2019, 115 countries implemented 294 reforms aimed at regulating business activities, most of which were implemented in such areas as business creation, obtaining building permits, connecting to the power supply system, taxation, optimization property registration processes, automation of logistics of international trade. The smallest number of reforms was recorded in the area of insolvency, bankruptcy and liquidation of enterprises. At the same time, only 1 % of the reforms were in low-income countries, and most of the reforms were implemented in middle-income countries. The Doing Business Rating is a tool for measuring the favorable business climate, the level of entrepreneurial activity and the level of corruption, the level of competitiveness of the country, which allows to identify priority areas for reform at the state level.
Keywords: international business conditions index Doing Business; economic security; business indicators; rating; operating environment